(untitled) (Research, Society and Development, 2023)
The elderly population has shown an increase in Brazilian demographic indices, in this sense, aging is correlated with reductions in muscle, bone and immune functionality, in which creatine supplementation has been presented as a therapy. The objective was to identify in the literature the influence of creatine on metabolism, distinguishing the effects and benefits. This is a descriptive research of the narrative literature review type, through online access to the PubMed MEDLINE, Scielo, Google Scholar, BVS and EBSCO databases, in December 2022. The keywords present in the descriptors in Health Sciences (DeCS) were used to search for works: “creatine”, “aging”, “sarcopenia” and “frailty”, totaling 21 materials for review after selection. Senility is configured by organic changes such as osteoporosis, sarcopenia, osteosarcopenia and immunosenescence. In this bias, creatine has benefits by stimulating the release of growth factors, the synthesis of anabolic proteins and the energy supply that enable the differentiation of satellite cells in muscle tissue and the predominance of osteoblastic action compared to osteoclastic action, enabling the therapy of the pathologies of senility. In addition, it plays an immunological role, mediated by the regulatory effect of chronic inflammation and inhibition of oxidative stress. Therefore, the viability of the use of dietary creatine supplementation in the elderly population is enshrined, requiring research directed at the group to adapt its nutritional application.